Calreticulin mediates an invasive breast cancer phenotype through the transcriptional dysregulation of p53 and MAPK pathways - Zamanian, Mohammadreza; Hamadneh, Lama Abdel Qader; Veerakumarasivam, Abhi; Abdul Rahman, Sabariah; Shohaimi, Shamarina; Rosli, Rozita (BioMed Central, 2016)
Background The introduction of effective novel biomarkers of invasion and metastasis is integral for the advancement of breast cancer management. The present study focused on the identification and evaluation of calreticulin (CRT) as a potential biomarker for breast cancer invasion.